Cytogenetic analysis of 1284 cases of Down syndrome - M.H Kariminejhad; R Kariminejhad; F Azimi; N Nabavi nia; K Alavi; M.T Takyar; Y Shafeghati (Journal of Kerman University of Medical Sciences, 1997)
Among 17786 karyotyres performed in our center,during 18 years (1357-1375),1300(7.3%) cases of chromosome 21 aberration,including 1284(98.77%) of Down syndrome have been detected.1191 of cases (92.76%) born free trisomy 21:61 cases (4.75%) revealed translocation and 32 cases (2.4%) showed mosaic pattern.among the pateints,59 had robertsonian translocation,2 had translocation between chromosome 21 and a non acrocentric chromosome designated as chromosomes 7 and 8.among the 1284 patients with chromosome 21 aberration,735 were male and 549 female with a Mto F ratio of 1.34:1-cytogenetic study of 18 parents of DS children with robertsonian translocation revealed that 4 cases(22.22%) were inherited from the carrier mothers.there were also 4 translocation in non G chromosomes,which were inherited from either parent.in general 8 of the 23 parents(34.78%) including 6 mothers and 2 fathers transmitted the involved chromosome to their children in the other 15 cases primary translocation occured.two of the DS were also associated with klinfelter syndrome (48,XXY+21) and one male child born 47,XY+21, 5p+Cri du chat).our findings are almost similar to the large group studies of other investigators.